1996
DOI: 10.1063/1.472770
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation energies of the molecules Bcl and Bcl+

Abstract: Dynamics of cluster dissociation following multiphoton ionization AIP Conf.The molecule BCl was generated by chlorination of B͑s͒ with both MgCl 2 and SrCl 2 in a heated effusive beam source, and identified by mass spectrometry. Gaseous equilibria in the B-Mg-Cl and B-Sr-Cl systems were studied in the regions 1350-1600 K and 1760-1830 K, respectively, and the dissociation energy D 0 ‫ؠ‬ ͑BCl͒ϭ121.3Ϯ1.1 kcal mol Ϫ1 ͑5.26Ϯ0.05 eV͒ was derived from thermochemical analysis. When compared with a dissociation limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 12 publications
10
18
0
Order By: Relevance
“…The closed shell chloroborane (BCl; X 1 Σ + ) molecule is isovalent to BF and CO, and erroneously described as a radical in two recent publications . The first part of Table collects CC and MRCI(+Q)/A6ζ spectroscopic parameters of BCl( X 1 Σ + ) along with experimental and theoretical results from Ref. .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closed shell chloroborane (BCl; X 1 Σ + ) molecule is isovalent to BF and CO, and erroneously described as a radical in two recent publications . The first part of Table collects CC and MRCI(+Q)/A6ζ spectroscopic parameters of BCl( X 1 Σ + ) along with experimental and theoretical results from Ref. .…”
Section: Resultsmentioning
confidence: 99%
“…PECs of BCl( X 1 Σ + ) and BCl − ( X 2 Π) are shown in Figure . As before an “experimental” binding energy of BCl − can be obtained based on the MRCI EA of BCl, EA 0 = −0.3 ± 0.11 eV, and the experimental values D 0 and EA of Cl:…”
Section: Resultsmentioning
confidence: 99%
“…These results are also tabulated in Table I. By careful comparisons, we have found that the R e and D e obtained at the relativistic corrections are closer to the experiments9, 19 than those determined at the nonrelativistic corrections at the same basis set, though the ω e value obtained at the relativistic corrections are further to the measurements12, 13, 18, 19 than that determined at the nonrelativistic corrections. As a whole, the relativistic corrections can give more accurate results.…”
Section: Computational Detailsmentioning
confidence: 54%
“…Such models need to include the spectroscopic data8. However, from the collected experimental spectroscopic parameters, we find that the dissociation energy, D 0 , of the BCl(X 1 Σ + ) has a history of dispute9, and the inconsistencies persist in the literature still up to date.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation